Konsep Kesakralan Masyarakat Emile Durkheim: Studi Kasus Suku Aborigin di Australia - Ahmad Zainal Mustofa (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2020)
This article explains the concept of community sacredness through the results of Emile Durkheim's research on Aboriginal tribes in Australia. The research method used is descriptive analytical. The results of this study are Emile Durkheim dividing people's trust into two groups, namely the sacred and the profane. These two things are very influential in people's daily lives. Besides these two things, religion also has a function to bind people's beliefs to obey the rules that apply in the environment. So it can be concluded that the sacredness of society occurs when they believe in the supernatural power possessed by totems, so that they glorify it and regard it as something sacred and have restrictions on anyone who violates it. Instead, they loosen the profane aspect as an earthly ritual, so they may violate it and ignore it.